Health-related physical fitness in men and women aged 17-26 years - Alex Ribeiro; Danilo Silva; Ferdinando Carvalho; Durcelina Schiavoni; Bruno Jesus; Edilson Cyrino (Revista Brasileira de Atividade Física e Saúde)
This study aimed to evaluate health-related physical fitness in male and female undergraduate students of Physical Education and Sports. Two hundred and fifty-seven 257 volunteer students aged 17 to 26 years (132 females and 125 males) underwent an antrhopometric assessment and motor fitness tests including sit-and-reach test (SRT), a modified abdominal fitness test (ABDT), and 12-minute run-walk test (12MRW). The results showed significant gender differences (p